2006
DOI: 10.1136/ijgc-00009577-200605000-00062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of uterine sarcomas: results from 14 years worth of experience in the Kinki district in Japan (1990–2003)

Abstract: To review clinical outcomes and therapeutic varieties, we were invited to submit data from the patients who were treated for uterine sarcomas in Japan from 1990 to 2003. Uterine sarcomas were defined as leiomyosarcoma (LMS), endometrial stromal sarcoma (ESS), and carcinosarcoma (CS). Of a total of 97 patients, 36 (37.1%) were diagnosed with LMS of the uterine corpus, 15 (15.5%) with ESS, 46 (47.4%) with CS. Median age at diagnosis was 59 (21–85) years. Clinical stages based on FIGO were 41 (42.3%) with stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Studies in the USA [6], France [7], and Italy [8] have reported serous-type BOTs as the most common (60-74), while studies in Korea [9] and Japan [10] have reported mucinous-type BOTs as the most common (68-76). However, these studies are too limited in number to reach firm conclusions about regional differences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the USA [6], France [7], and Italy [8] have reported serous-type BOTs as the most common (60-74), while studies in Korea [9] and Japan [10] have reported mucinous-type BOTs as the most common (68-76). However, these studies are too limited in number to reach firm conclusions about regional differences.…”
Section: Introductionmentioning
confidence: 99%
“…OVARIAN MUCINOUS CYSTIC tumors (MCT) are categorized as benign, borderline, and malignant based on histological features, with benign mucinous cystadenoma (MC) accounting for 80% and borderline MC being the predominant category in the remainder . Borderline MC is characterized by a lack of stromal invasion, a low malignant potential, possible peritoneal implants, frequent recurrence, and good prognosis . The surgical approach is different between benign and borderline MCs.…”
mentioning
confidence: 99%
“…For borderline MC, patients who wish to preserve fertility can undergo the conservative surgery of unilateral salpingo‐oophorectomy. Other patients need the radical surgical excision . Surgical strategy is determined often on the intraoperative frozen section diagnosis.…”
mentioning
confidence: 99%
“…In our study, the only three parameters that were significantly associated with a poor outcome in a multivariable Cox regression model were FIGO stage (hazard ratio, 5.239), a PHH3 score of ≥29/10 HPFs (hazard ratio, 2.713), and age (hazard ratio, 1.060) (Table ). Stage appears to be the most consistent and significant prognostic indicator in the literature . However, recurrence and metastasis among patients with stage I LMS are not uncommon .…”
Section: Discussionmentioning
confidence: 91%